ECOLOGICAL TEST OF A NEW HALF-FAST ONION VARIETY FOR AN ANNUAL CULTURE IN THE REPUBLIC OF MARI EL - M. G. Ibragimbekov; O. R. Davletbaeva; А. N. Khovrin (Овощи России)
In terms of occupied areas, onion is on the third place in the world among vegetable crops, second only to tomato and watermelon. In Russia, onion is grown on an area of 88 to 96 thousand hectares of onions, and ranks third, yielding to cabbage and tomato.The increase in the production of onions is not only due to the increase in the areas occupied by the crop, but also due to increased yields. This is achieved by introducing new highly productive varieties and hybrids into production, increasing the overall cropping culture and the level of cultivation technology. Along with the creation of heterotic hybrids at the present time, the Russian Federation also continues to select varieties that show high rates when grown in a oneyear crop. The results of production tests of a new onion variety of Forward Selected Breeding VNIIO a branch of the FGBNU FNCO has shown that it is promising because it has a high yield potential, high quality of bulbs and excellent preservation in conditions of repositories with controlled conditions. Characterized by mid-maturity maturation. The period from full shoots to mass lodging of leaves is 110 days. In relation to the longitude of the day, the forward sort refers to a group of long-day bows. The bulb is bilobate, rounded and rounded – flat, with an average mass of 90-120 g. The color of the dry covering scales is yellow-brown, the succulent scales are greenish. The taste is semi-sharp. The dry matter content in the bulb during the test years was 11.0-12.0%.